Decreased histone deacetylase 2 impairs Nrf2 activation by oxidative stress. - Mercado,N; Thimmulappa,R; Thomas,CM; Fenwick,PS; Chana,KK; Donnelly,LE; Biswal,S; Ito,K; Barnes,PJ (Biochem Biophys Res Commun, 2011)
Nuclear factor erythroid 2-related factor 2 (Nrf2) plays a crucial role in cellular defence against oxidative stress by inducing the expression of multiple anti-oxidant genes. However, where high levels of oxidative stress are observed, such as chronic obstructive pulmonary disease (COPD), Nrf2 activity is reduced, although the molecular mechanism for this defect is uncertain. Here, we show that down-regulation of histone deacetylase (HDAC) 2 causes Nrf2 instability, resulting in reduced anti-oxidant gene expression and increase sensitivity to oxidative stress. Although Nrf2 protein was clearly stabilized after hydrogen peroxide (H(2)O(2)) stimulation in a bronchial epithelial cell line (BEAS2B), Nrf2 stability was decreased and Nrf2 acetylation increased in the presence of an HDAC inhibitor, trichostatin A (TSA). TSA also reduced Nrf2-regulated heme-oxygenase-1 (HO-1) expression in these cells, and this was confirmed in acute cigarette-smoke exposed mice in vivo. HDAC2 knock-down by RNA interference resulted in reduced H(2)O(2)-induced Nrf2 protein stability and activity in BEAS2B cells, whereas HDAC1 knockdown had no effect. Furthermore, monocyte-derived macrophages obtained from healthy volunteers (non-smokers and smokers) and COPD patients showed a significant correlation between HDAC2 expression and Nrf2 expression (r=0.92, p<0.0001). Thus, reduced HDAC2 activity in COPD may account for increased Nrf2 acetylation, reduced Nrf2 stability and impaired anti oxidant defences.